European headache federation guideline on the use of monoclonal antibodies acting on the calcitonin gene related peptide or its receptor for migraine prevention - Sacco, Simona; Bendtsen, Lars; Ashina, Messoud; Reuter, Uwe; Terwindt, Gisela; Mitsikostas, Dimos-Dimitrios; Martelletti, Paolo (Journal of headache and pain, 2019)
Background and aim Monoclonal antibodies acting on the calcitonin gene-related peptide or on its receptor are new drugs to prevent migraine. Four monoclonal antibodies have been developed: one targeting the calcitonin gene-related peptide receptor (erenumab) and three targeting the calcitonin gene-related peptide (eptinezumab, fremanezumab, and galcanezumab). The aim of this document by the European Headache Federation (EHF) is to provide an evidence-based and expert-based guideline on the use of the monoclonal antibodies acting on the calcitonin gene-related peptide for migraine prevention. Methods The guideline was developed following the Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) approach. The working group identified relevant questions, performed systematic review and analysis of the literature, assessed the quality of available evidence, and wrote recommendations. Where the GRADE approach was not applicable, expert opinion was provided. Results We found low to high quality of evidence to recommend eptinezumab, erenumab, fremanezumab, and galcanezumab in patients with episodic migraine and medium to high quality of evidence to recommend erenumab, fremanezumab, and galcanezumab in patients with chronic migraine. For several clinical questions, there was not enough evidence to provide recommendations using the GRADE approach and recommendations relied on experts’ opinion. Conclusion Monoclonal antibodies acting on the calcitonin gene-related peptide are new drugs which can be recommended for migraine prevention. Real life data will be useful to improve the use of those drugs in clinical practice.